Depressão e ansiedade na adolescência: o papel do baixo peso ao nascer e dos polimorfismos no sistema galaninérgico - Machado, Fernanda da Conceição Costa [UNIFESP] (2016)
This thesis has been divided into two chapters. In the first chapter, the objective was to determine whether adolescents, with a history of low birth weight, are more likely to report symptoms of depression/anxiety. Therefore, a cross-sectional study, with 102 adolescents (40 boys and 62 girls) aged 10-18 years was conducted. It was observed that the incidence of depression symptoms among this population was present in 63% of the adolescents stratified in the first quartile of birth weight, while only 20% of adolescents in the last quartile reported the presence of these symptoms. Similarly, when assessing the symptomatology of anxiety, it was verified that 83% of the adolescents in the first quartile presented the symptoms, followed only by 36% in the last quartile of birth weight. The logistics analysis showed that female adolescents are 4.9 times more likely to have symptoms of anxiety when compared with male adolescents. In addition, it was observed that the adolescents, whose birth weight was in the first quartile, showed 8,4 times more chances to present the anxiety symptoms. On the other hand, adolescents who reported a physical activity practice greater than or equal to two times a week showed 72% chance to develop anxiety symptoms. Similar results were observed when considering the depressive symptomatology. It was also observed that the female adolescents were 3.9 times more likely to have symptoms of depression, and adolescents in the first quartile of birth weight presented 5.6 times more chances to develop depression. However, the regular practice of physical activity was effective to reduce the chance of developing depression symptoms in 77%. Thus, it is concluded that the study confirms the finding in literature showing that low birth weight is correlated with higher rates of symptoms of depression and anxiety during adolescence. Therefore, the presence of a deleterious fetal environment appears to have a significant impact on the presence of psychiatric disorders. In the second chapter, we sought to investigate the importance of single nucleotide polymorphisms (SNPs) in the galaninergic system, and the presence of depression symptoms and anxiety. For this, a cross-sectional study with 87 pubescent adolescents (51 girls and 36 boys) was realized, evaluating the following SNPs: rs948854 and rs4432027 present in the gene promoter region encoding galanin (GAL), rs11665337 found in the GALR1 receptor and the rs8836 present in GALR2. We verified that, only in relation to the SNPs rs948854 and rs11665337, the adolescents carrying the GG and AG genotype had median scores of CDI significantly higher than adolescents homozygous AA, suggesting that carriers of the G allele for these SNPs have certain genetic vulnerability to develop depression. The same was not observed for the SCARED score. Moreover, we found no significant changes in the scores of CDI and SCARED when analyzing SNPs rs4432027 and rs8836. Finally, we observed no significant differences regarding the distribution of genotypes for the different SNPs of the galaninergic system in relation to race, gender and current nutritional status of the population studied. Therefore, it is concluded that the SNP rs948854 which is located in the promoter gene region of the GAL gene, as well as the SNP rs11665337 present in GALR1 receptor, seem to be involved in the modulation of depressive state, especially in those individuals with genotypes AG and GG. However, we found no relationship between the different SNPs in galaninergic system with the presence of anxiety disorders. This study reinforces and complements the findings in the literature on the importance of genetic variations in the gene encoding GAL and its GALR1 receptor on depressive symptoms.